Development of a prototype kitchen cutting equipment memo dissertation 2 / Mukhriz Azizi - Azizi, Mukhriz (2023)
This project prototype has become a mark on the innovation of kitchenware tools or equipment in general. The prototype had innovated kitchen equipment significantly in terms of portability, efficiency, and safety. This project prototype had also increased safety for all users at homes. This product is made to enhance safety especially when the item itself is left unattended. Therefore, children are away from the risks of injuries that may occur without safe kitchen tools.